Vegetated Buffer Zone Restoration Planning in Small Urban Watersheds - Yucong Duan (MDPI AG, 2021)
Vegetated buffer zones (VBZ) are accepted worldwide as a low impact method to avoid non-point source pollution and restore the balance of river ecosystems. Strongly influenced by industrialization and urbanization, urban river ecology is seriously damaged, and restoration is tricky. This study established a complete buffer zone construction framework suitable for the small urban watershed, and its feasibility is verified in a small watershed in Northern China. First, common plants in the study area were selected to test their ability to purify pollutants, and plant combinations were optimized. Secondly, according to the field investigation, the reference buffer zone was determined, and its sewage interception capacity was tested through a runoff simulation experiment. Then, based on GIS and Phillips time and hydraulic models, the normal buffer width of the study area was obtained; 60 m for mainstream and 40 m for tributaries. By optimizing the vegetation scheme and delimiting an efficient buffer zone, the land occupation can be reduced by 17%. Finally, combined with the characteristics of different river sections, an elaborate VBZ restoration scheme is designed from the aspects of vegetation, planning, and zoning. Generally, this research will provide government and land managers scientific and practical ideas and technologies to formulate a land management policy for urban river buffer zones in order to find a balance between aquatic ecological protection and urban land use planning and optimize the allocation of construction funds.